2023
DOI: 10.1002/eji.202350433
|View full text |Cite
|
Sign up to set email alerts
|

Serum TGF‐β as a predictive biomarker for severe disease and fatality of COVID‐19

Abstract: For targeted intervention in coronavirus disease 2019 (COVID‐19), there is a high medical need for biomarkers that predict disease progression and severity in the first days after symptom onset. This study assessed the utility of early transforming growth factor β (TGF‐β) serum levels in COVID‐19 patients to predict disease severity, fatality, and response to dexamethasone therapy. Patients with severe COVID‐19 had significantly higher TGF‐β levels (416 pg/mL) as compared to patients with mild (165 pg/mL, p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Frischbutter et al showed that patients with severe disease have significantly higher serum concentrations of TGF-β than subjects with moderate or mild COVID-19. They also showed that TGF-β could be used as a predictor of disease fatality, as a higher concentration of this cytokine was found in patients who died than in survivors [20]. A similar positive correlation of TGF-β with the severity of COVID-19 was also found by Susak et al [21].…”
Section: Discussionsupporting
confidence: 53%
“…Frischbutter et al showed that patients with severe disease have significantly higher serum concentrations of TGF-β than subjects with moderate or mild COVID-19. They also showed that TGF-β could be used as a predictor of disease fatality, as a higher concentration of this cytokine was found in patients who died than in survivors [20]. A similar positive correlation of TGF-β with the severity of COVID-19 was also found by Susak et al [21].…”
Section: Discussionsupporting
confidence: 53%
“…The development of severe COVID-19 following infection with SARS-CoV-2 has been associated with pronounced systemic levels of TGF-β early after infection [79]. Moreover, in a followup study, early levels of TGF-β were identified as a predictor of disease severity and fatality [80]. Although mild and moderate COVID-19 are characterized by activated NK cells that efficiently control SARS-CoV-2 replication in vitro, TGF-β pervasively suppresses antiviral functions of in severe disease [79] (Fig.…”
Section: Sars-cov-2 Infection-mediated Induction Of Tgf-βmentioning
confidence: 97%